Attitudes and practices on antibiotic use and its emerging threats among Lebanese dairy veterinarians: a case study from a developing country - Dankar, Iman; Hassan, Hussein F.; Serhan, Mireille (Frontiers in Veterinary Science, 2023)
This study aimed to explore how veterinarians (vets) rationalized their prescribing decisions for antimicrobial (AM) uses, the barriers they perceived to implement proper farm management in Lebanon, and the consecutive threats that might arise concerning the emergent spread of antimicrobial resistance in animals and the population. Amid the COVID-19 pandemic, phone call interviews were conducted with 34 veterinarians working in different demographic regions across the country. Data were analyzed qualitatively using an inductive thematic analysis. The majority of veterinarians called for responsible antibiotic use. The prescribing decision of veterinarians was based mainly on suspected disease from field examination, farmer's reports via phone calls, and the ability of the farmer to cover antibiotic costs. Very few veterinarians referred to laboratory diagnosis before prescribing a specific AM due to many obstacles. This study uncovered the absence of a trust relationship between veterinarians and farmers in Lebanon. Veterinarians provided different insights into farming practices, reflecting that farmers, in general, lack proper knowledge and implementation of farm management and that they mainly treat the 2 herd on their own, especially in light of the current unprecedented economic crisis that Lebanon has been facing in the last three years. Above all, veterinarians revealed that AM resistance in Lebanon is markedly spreading, which calls for a serious and instantaneous set of governmental policies and regulations.